La gestión pública y el uso del SIAF en el Instituto de Investigaciones de la Amazonía Peruana, Iquitos 2022 - Saberbein Caballero, Roberto Ronnel (2023)
In the present research work, the objective was to determine the relationship between public management and the use of the SIAF in the Research Institute of the Peruvian Amazon, Iquitos 2022, choosing to be an applied study of a descriptive-correlational level with a non-experimental design, where we have worked with 93 workers, for the data collection the survey and questionnaire have been used. Therefore, it was concluded that public management has been developing very efficiently, because the entity always uses strategic plans as a tool to establish actions to achieve institutional goals. On the other hand, optimal use has been made of the SIAF, since it always systematizes the accounting in the commitment phases and is formalized through cash receipts. Finally, it is determined that there is a relationship between the variables, being corroborated by a coefficient and a significance of (r=0.594; p=0.000).